The Combination of Schisandrol B and Wedelolactone Synergistically Reverses Hepatic Fibrosis Via Modulating Multiple Signaling Pathways in Mice - Ai, Yongqiang; Shi, Wei; Zuo, Xiaobin; Sun, Xiaoming; Chen, Yuanyuan; Wang, Zhilei; Li, Ruisheng; Song, Xueai; Dai, Wenzhang; Mu, Wenqing; Ding, Kaixin; Li, Zhiyong; et al. (Frontiers in Pharmacology, 2021)
Hepatic fibrosis represents an important event in the progression of chronic liver injury to cirrhosis, and is characterized by excessive extracellular matrix (ECM) proteins aggregation. Early fibrosis can be reversed by inhibiting hepatocyte injury, inflammation, or hepatic stellate cells (HSCs) activation, so the development of antifibrotic drugs is important to reduce the incidence of hepatic cirrhosis or even hepatic carcinoma. Here we demonstrate that Schisandrol B (SolB), one of the major active constituents of traditional hepato-protective Chinese medicine, Schisandra sphenanthera, significantly protects against hepatocyte injury, while Wedelolactone (WeD) suppresses the TGF-β1/Smads signaling pathway in hepatic stellate cells (HSCs) and inflammation, the combination of the two reverses hepatic fibrosis in mice and the inhibitory effect of the combination on hepatic fibrosis is superior to that of SolB or WeD treatment alone. Combined pharmacotherapy represents a promising strategy for the prevention and treatment of liver fibrosis.